2014
DOI: 10.1002/2013ja019096
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter radar‐FAST satellite common volume observations of upflow‐to‐outflow conversion

Abstract: Incoherent scatter radar measurements from the Sondrestrom Research Facility and the European Incoherent Scatter Svalbard radar have been combined with all-sky images, polar convection measurements, and FAST particle and field measurements to quantify the contribution of different magnetosphere-ionosphere coupling processes to the extraction efficiency of ions from the ionosphere. Upflowing ions are traced from their source vertically and horizontally to determine where and when they are likely to intersect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…The adaptive time stepping of the model is such that stability is retained at every time step, and a typical time step is ∼0.5 s. The model was run to a steady state for the initial conditions, and all of the simulations start at 15 UT creating a consistent set of background conditions for each run. The simulation results presented here use a dipole mesh [ Huba et al , ; Zettergren and Snively , ] spanning L shells 12–16, centered roughly on the location of the Sondrestrom research facility on the west coast of Greenland ∼(67°, 309°), a location of interest for ion upflow [ Semeter et al , ; Zettergren et al , ; Sánchez and Stømme , ]. For this study, GEMINI‐TIA was run for multiple combinations of DC electric fields, transverse wave heating, and neutral winds implemented using the configurations described in paragraphs below.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptive time stepping of the model is such that stability is retained at every time step, and a typical time step is ∼0.5 s. The model was run to a steady state for the initial conditions, and all of the simulations start at 15 UT creating a consistent set of background conditions for each run. The simulation results presented here use a dipole mesh [ Huba et al , ; Zettergren and Snively , ] spanning L shells 12–16, centered roughly on the location of the Sondrestrom research facility on the west coast of Greenland ∼(67°, 309°), a location of interest for ion upflow [ Semeter et al , ; Zettergren et al , ; Sánchez and Stømme , ]. For this study, GEMINI‐TIA was run for multiple combinations of DC electric fields, transverse wave heating, and neutral winds implemented using the configurations described in paragraphs below.…”
Section: Resultsmentioning
confidence: 99%
“…If the reference values are not optimized to this event or if the precipitating electron flux is too low, the ambipolar electric field will suffer and outflow will be reduced. Another possibility is the necessity for additional acceleration mechanisms, such as wave‐particle transverse heating effects [ Andre and Yau , ; Chaston et al , ], which is frequently observed to increase ion upflows [ Norqvist et al , ; Sánchez and StrØmme , ]. These issues require further investigation and potential improvements to the PWOM model but are not likely to diminish enhancement of oxygen outflows resulting from ring current‐driven region 2 FACs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The mirror force converts these perpendicular distributions to parallel outflow. Sánchez and Strømme (2014) examined the efficiency of the two‐step process by tracing the low‐altitude upflowing ions observed using incoherent scatter radar measurements to the higher altitude acceleration region measured by the FAST satellite. They found that the extraction efficiency, which represents the percentage of the ionosphere ions lost, ranged from 0.1% to 5%, depending on the wave amplitude.…”
Section: Introductionmentioning
confidence: 99%